NALAR KRITIS POLIGAMI SEBAGAI KEKERASAN DALAM RUMAH TANGGA: (Analisis Terhadap Undang-Undang KDRT Nomor 23 Tahun 2004) - Sugitanata, Arif; Karimullah, Suud Sarim (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
In this paper, the researcher analyses and explains polygamy as a form of domestic violence from the perspective of positive Indonesian law and how it critiques Law No. 1 of 1974 on Marriage by examining Law No. 23 of 2004 on the Elimination of Domestic Violence in Indonesia. Using a literature review, this study found that polygamy carried out without fulfilling the conditions stipulated in the marriage law and Islamic Law Compilation (KHI) can be a form of domestic violence. This is because polygamy committed without the first wife's consent and without regard to the family's welfare can cause injustice and imbalance in the husband-wife relationship and damage the family concerned. Polygamy cases, if associated with Law No. 23 of 2004 concerning the elimination of domestic violence, are a form of psychological violence that can be criminalised and charged with Domestic Violence Law No. 23 of 2004, specifically Article five, which states that